Advertisement Remove all ads

Simplify the following and express in the form a + ib: (1 + 3i)2 (3 + i) - Mathematics

Sum

Simplify the following and express in the form a + ib:

(1 + 3i)2 (3 + i)

Advertisement Remove all ads

Solution

(1 + 3i)2 (3 + i)
= (1 + 6i + 9i2)(3 + i)
= (1 + 6i – 9)(3 + i)        ...[∵ i2 = – 1]
= (– 8 + 6i)(3 + i)
=  – 24 – 8i + 18i + 6i2
= – 24 + 10i +6(– 1)
= –24 + 10i – 6
= – 30 + 10i

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Balbharati Mathematics and Statistics 1 (Commerce) 11th Standard Maharashtra State Board
Chapter 3 Complex Numbers
Miscellaneous Exercise 3 | Q 3. (v) | Page 42
Advertisement Remove all ads

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×